2003
DOI: 10.1046/j.1365-2958.2003.03768.x
|View full text |Cite
|
Sign up to set email alerts
|

The NblAI protein from the filamentous cyanobacterium Tolypothrix PCC 7601: regulation of its expression and interactions with phycobilisome components

Abstract: SummaryCyanobacteria respond to changes in light or nutrient availability by modifications in their photosynthetic light harvesting antenna. In unicellular cyanobacteria a small polypeptide (NblA) is required for phycobilisome degradation following environmental stresses. In the filamentous strain Tolypothrix sp. PCC 7601 the nblAI gene, encoding a NblA homologue, is located upstream of the operon coding for phycoerythrin ( cpeBA ). The nblAI transcripts all originate from a single transcription start point; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…Although it has been shown that NblA binds to phycobiliproteins (22,25), the exact function of the NblA protein has not yet been elucidated. Here we provided evidence for an interaction between NblA and ClpC, suggesting that PBS degradation occurs via a Clp protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown that NblA binds to phycobiliproteins (22,25), the exact function of the NblA protein has not yet been elucidated. Here we provided evidence for an interaction between NblA and ClpC, suggesting that PBS degradation occurs via a Clp protease.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence and structure of NblA show no significant similarity to proteins with known function, and the molecular mechanism of NblA action in PBS degradation is not clear. In vitro studies showed that NblA interacts with the ␣-subunits of phycobiliproteins (22,25). Furthermore, results of binding experiments with variants of NblA carrying amino acid substitutions at various positions provided evidence that the interaction with phycobiliproteins is mediated via conserved amino acid residues near its C terminus (25).…”
mentioning
confidence: 89%
“…In a recent study we have shown that this 15 kDa form -a dimer or a complex formed by NblAI and another small molecule -is always present, and that the~7 kDa form does exist but it is only found at such a molecular mass when associated with phycobiliproteins. Such a situation only occurs when cells are grown under red light, conditions under which both the 15 and 7 kDa proteins coexist (Luque et al, 2003). The NblAI increase observed in the three Tolypothrix sp.…”
Section: Expression Of Nblaimentioning
confidence: 98%
“…Complete genomic sequences revealed that in some strains there may exist up to four nblA gene copies. Based on sequence similarities, the Tolypothrix PCC 7601 nblA gene that we have studied was designated nblAI (Luque et al, 2003), and this name will be used throughout. Anti-NblAI antibodies were raised and used to probe extracts from cells grown under nitrogendepleted and nitrogen-replete conditions.…”
Section: Introductionmentioning
confidence: 99%
“…16 Therefore, the effect of changes in nitrogen availability on TSPO mRNA levels was assessed before and after exposing F. diplosiphon cells to changes in nitrogen availability (Fig. 5).…”
Section: Various Environmental Cues Have Different Impacts On Distincmentioning
confidence: 99%